Kepentingan Amerika Serikat dalam Membangun United States Ground-based Midcourse Defense (US GMD) di Polandia - Sukmatika, Anak Agung Yumas; Dewi, Putu Ratih Kumala; Parameswari, Anak Agung Ayu Intan (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2017)
This study analyzed the reasons behind US anti-missile defense shield construction called United States Ground-based Midcourse Defense (US GMD) which was located in Eastern Europe, Poland, during George W. Bush prescidency (2001-2008). The efforts of maintaining unipolarity and minimizing any threats in order to weaken the US was crucially to be done due to the US was experiencing transitional phase from unipolar to multipolar at that time. Related to this issue, the United States mapped Iran as a potential threat as well as an “axis of evil” since it was rapidly developing the ballistic missiles which resulted in threatening the US security and unipolarity. Iran was even considered as a country which capable of carrying the nuclear warheads without any warning. Through a qualitative methodology, this study found that the main purpose of building the US GMD in Poland was to maintain US hegemonic stability in Europe. The stability of hegemony was derived from an important combination of defense, economy, ideology, and world order. Therefore, the reason behind US GMD construction in Poland was to achieve the US national interests in the form of defense, economy, ideology as well as the world order, which then confirmed the stability of US hegemony in Europe. Keywords: US GMD, hegemonic stability